2017
DOI: 10.1186/s12912-017-0217-3
|View full text |Cite
|
Sign up to set email alerts
|

Consulted ethical problems of clinical nursing practice: perspective of faculty members in Japan

Abstract: BackgroundThere are several studies that have targeted student nurses, but few have clarified the details pertaining to the specific ethical problems in clinical practice with the viewpoint of the nursing faculty. This study was to investigate the ethical problems in clinical practice reported by student nurses to Japanese nursing faculty members for the purpose of improving ethics education in clinical practice.MethodThe subjects comprised 705 nursing faculty members (we sent three questionnaires to one unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Such experiences cause a decrease in motivation among students. 20 The teacher-student relationship is a power relationship based on students' dependence on teachers' professional knowledge, skills, and authority by its nature. Clinical educators and health professionals are required to adopt a respectful attitude so that they can influence students both professionally and personally, and increase students' motivation to learn.…”
Section: Discussionmentioning
confidence: 99%
“…Such experiences cause a decrease in motivation among students. 20 The teacher-student relationship is a power relationship based on students' dependence on teachers' professional knowledge, skills, and authority by its nature. Clinical educators and health professionals are required to adopt a respectful attitude so that they can influence students both professionally and personally, and increase students' motivation to learn.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, other studies revealed that the implementation of educational plans is not in a way that fosters creative and critical thinking in students, so they are not able to apply their knowledge in clinical situations. Besides, there is no appropriate psychological support from instructors in clinical settings (3,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that students should be provided with an opportunity to associate classroom learning with what occurred in practical training. [40] To improve this situation, it seemed to be effective for nursing ethics educators to cooperate with teachers in charge of practical training to examine what and how students should learn in classes. However educators have not fully discussed improving ethical skills of nursing students through nursing education.…”
Section: Discussionmentioning
confidence: 99%